1993
DOI: 10.1073/pnas.90.24.11633
|View full text |Cite
|
Sign up to set email alerts
|

Rapid solution assays for retroviral integration reactions and their use in kinetic analyses of wild-type and mutant Rous sarcoma virus integrases.

Abstract: A rapid method for quantitating products of the oligodeoxynucleotide processing reaction in vitro has been developed to facilitate enzymatic studies of the retroviral integrases. Unlike earlier procedures, this assay does not depend on polyacrylamide gel electrophoresis but separates products by batch adsorption to PEI-cellulose. A joining assay has also been modified, to facilitate measurement of the two distinct steps in the integration reaction under parallel conditions. Since these methods allow quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…We previously reported that the optimal pH for the full-length wild type ASV IN was ϳ9 (16). Using the IN catalytic core domain as well as the full-length wild type IN protein, we carried out a standard assay for IN processing and endonuclease activity.…”
Section: Conformation Of Asp/asn-64 -mentioning
confidence: 99%
“…We previously reported that the optimal pH for the full-length wild type ASV IN was ϳ9 (16). Using the IN catalytic core domain as well as the full-length wild type IN protein, we carried out a standard assay for IN processing and endonuclease activity.…”
Section: Conformation Of Asp/asn-64 -mentioning
confidence: 99%
“…) INs (30,31). However, a much lower value for the processing rate (0.24 hr Ϫ1 ) was measured for HIV-1 IN using fluorescence resonance energy transfer (32).…”
mentioning
confidence: 99%
“…The initial exponential phase represents the actual reactivity of the enzyme with respect to both binding specificity and catalytic rate. In addition, the initial exponential phase arises as a direct consequence of a slow post-chemistry step in the reaction mechanism and generally reflects a slow rate-limiting product release step (35). In these instances, a faster steadystate turnover typically reflects only a faster rate of product release (21, 36 -39).…”
Section: Presteady-state Analysis Of a Novel Splicing Reaction-mentioning
confidence: 99%